Peningkatan Kreativitas dan Motivasi Belajar Pembelajaran IPA Melalui Strategi Group Investigation Pada Siswa Kelas IV SDN 1 Kemloko Godong Grobogan Tahun Ajaran 2015/2016 - Fungkisari, Siti Widia, Drs. Mulyadi S. K., SH.,M.Pd (2016)
This research purpose to knowing : (1) an increase the student creativity on sains learning class iv sdn 1 kemloko use Group Investigation strategy, (2) to increased motivated studying on the sains learning class iv sdn 1 kemloko using group investigation strategy. The subject in this research is all student class ivsdnkemloko which amounts to 27 student.the technic data collection is use method observation, interview, and documentation. Instruments of data collection for this research using observation sheet that is applied to teachers and students.The result of this observation showing that there is an increasing in the level of creativity and student's motivation is proven through two cycles that have been done. in cycle I meeting I percentage of student creativity is 72,84%, and learning motivation is 74,38%. In cycle 1 meeting 2 from these two variables have been increased, percentage student's creativity is 77,16%, and learning motivation is 76,85%. In cycle II meeting 1 the percentage student's creativity is 78,40% and the percentage learning motivation is 78,70%. In cycle II meeting 2 percentage of student creativity is 85,80%, and percentage learning motivation is 85,19%. The concluded on studied using the strategy of group investigation can increasedthe creativity and student learning motivation in sains studying class iv sd n 1 kemloko godong 2015/2016.